2002
DOI: 10.1108/01439910210440264
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics, design and control of the 6‐PSU platform

Abstract: The Department of Mechanical Engineering at Ohio University has designed, constructed, and controlled a new 6‐dof in‐parallel‐actuated platform, a combination and modification of existing designs. The 6‐PSU platform consists of six legs with a prismatic joint, spherical joint, and universal joint connecting links in each leg which move the platform in the six Cartesian freedoms with respect to the base. The prismatic joint is actuated while the other two joints in each leg are passive. The six prismatic joints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…It has been shown that because of the freedom possessed by the joints, given the length of the actuators it is possible to find up to 40 positions of the platform that satisfy equation (3) [4], [11]- [13]. Nevertheless, most of the studies refer to the 6-UPS platform, and very few [6], [13], [14] analyze its variant 6-PUS.…”
Section: Direct and Inverse Kinematicsmentioning
confidence: 98%
“…It has been shown that because of the freedom possessed by the joints, given the length of the actuators it is possible to find up to 40 positions of the platform that satisfy equation (3) [4], [11]- [13]. Nevertheless, most of the studies refer to the 6-UPS platform, and very few [6], [13], [14] analyze its variant 6-PUS.…”
Section: Direct and Inverse Kinematicsmentioning
confidence: 98%
“…There are two frames describing the motion of the moving plate (Hopkins and Williams, 2002): an inertia frame (Xa, Ya, Za) located at the center of the base plate and a body frame (Xb, Yb, Zb) located at the center of the moving plate with Zb‐axis pointing outward (Figure 3). The length vector of the i th leg is calculated as: Equation 20 In which, A i A is the position of the lower joint A i in the inertia frame, B i A is the position of the upper joint B i in the inertia frame: Equation 21 In which, A T B is the transformation matrix form the body frame (Xb, Yb, Zb) to the inertia frame (Xa, Ya, Za), B i B is the position of the upper joint B i in the plate body frame.…”
Section: Inverse Kinematics Based On Coupling Compensationmentioning
confidence: 99%
“…As a result, a comprehensive methodology for direct controlling from manipulators to the end effector was missed. Consequently, using the position control methodology solely limits the robot design to the joint space (Hopkins and Williams, 2002). In particular, the control methodologies based on the inverse dynamic are substantial to control the end effector motion through the manipulators, directly.…”
Section: Introductionmentioning
confidence: 99%